ผลของการจัดกิจกรรมการเรียนรู้พลศึกษาโดยใช้โปรแกรมการออกกำลังกายแบบฟูลบอดี้เอ๊กเซอร์ไซส์ที่มีต่อสมรรถภาพทางกายที่สัมพันธ์กับสุขภาพของนักเรียนมัธยมศึกษาตอนต้น - สุรศักดิ์ เขตชัยภูมิ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this research was to study and to compare the effect of physical education learning management by using a full-body exercise on health-related physical fitness of the lower secondary school students, the subjects were 40 students; aged between 12 – 15 years old. They were divided equally into two groups: control group were 20 students and the experimental group were 20 students. Health-related physical fitness was measured before and after the experiment. The experimental group exercised for 60 minutes a day (warmed up 5 minutes; worked out 45 minutes; cooled down 5 minutes; summary 5 minutes), and 3 days a week. The obtained data were statistically analyzed in term of the means and standard deviations. The t-test was employed to determine the significant differences at .05 levels. The results were as follows: 1. After experimental in 8 weeks, health-related physical fitness in the experimental group were developed better than before experiment all the test items at the significant difference at the .05 level. 2. After experimental in 8 weeks, health-related physical fitness of the experimental group was developed better than the control group in the test item of body mass index at the significant difference at .05 level. Conclusion: Physical education learning management by using a full-body exercise program could be improved health-related physical fitness of the lower secondary school students lower standard criteria.